2001
DOI: 10.2105/ajph.91.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Are we headed for a resurgence of the HIV epidemic among men who have sex with men?

Abstract: HIV remains a critical health issue for men who have sex with men (MSM). In the United States, an estimated 365,000 to 535,000 MSM are living with HIV, and 42% of new HIV infections occur in this population. Recent data on sexually transmitted diseases and on sexual behavior indicate the potential for a resurgence in HIV infections among MSM. Outbreaks of gonorrhea and syphilis have been reported in a growing number of cities, and several studies have observed an increase in unprotected anal intercourse among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(27 citation statements)
references
References 81 publications
2
25
0
Order By: Relevance
“…62,65–74 This was attributed to ‘an abandonment of safer sex practices among some gay and bisexual men’ 75 , with concerns about an emerging syndemic (i.e. synergistic epidemics of HIV, STIs, substance use, etc.).…”
Section: The Fall and Subsequent Rise In Syphilis Among Msmmentioning
confidence: 99%
“…62,65–74 This was attributed to ‘an abandonment of safer sex practices among some gay and bisexual men’ 75 , with concerns about an emerging syndemic (i.e. synergistic epidemics of HIV, STIs, substance use, etc.).…”
Section: The Fall and Subsequent Rise In Syphilis Among Msmmentioning
confidence: 99%
“…The argu-ment went on that it was best to look at HIV/AIDS not as a microbial health challenge but rather as both behavioral and environmental challenge in the design of interventions and mitigation. This would allow time to lead the way by way of strategy (Wolitski, Valdiserri, Denning, & Levine, 2001).…”
Section: The "Exceptionalism" Debate On Hiv and Aids In The Western Imentioning
confidence: 99%
“…Extant literature has described lower concern about HIV transmission and increased sexual risk taking due to the availability of highly active anti-retroviral treatment (HAART) for HIV-positive individuals and pre-exposure prophylaxis (PrEP) for HIV-negative individuals (Brooks et al, 2011; Hoff et al, 2015; Liu et al, 2013; Ostrow et al, 2002; Venkatesh et al, 2010). The widespread availability of HAART in 1996 led to dramatic declines in AIDS and HIV-related deaths by reducing the viral load of HIV-infected individuals, which, coupled with behavioral interventions, decreased HIV incidence during that time (Detels et al, 1998; Hammer et al, 1997; Wolitski, Valdiserri, Denning, & Levine, 2001). Similarly, PrEP use among HIV-negative MSM has implications for sexual behavior; up to 36% of Black MSM (BMSM; including homosexual and bisexual men) reported that they would be likely to decrease their condom use while on PrEP (Brooks et al, 2011; Golub, Kowalczyk, Weinberger, & Parsons, 2010; Tripathi, Whiteside, & Duffus, 2013).…”
Section: Introductionmentioning
confidence: 99%